Generation of an immortalized mouse embryonic palatal mesenchyme cell line - Fantauzzo, Katherine A. (PLoS One, 2017)
Palatogenesis is a complex morphogenetic process, disruptions in which result in highly prevalent birth defects in humans. In recent decades, the use of model systems such as genetically-modified mice, mouse palatal organ cultures and primary mouse embryonic palatal mesenchyme (MEPM) cultures has provided significant insight into the molecular and cellular defects underlying cleft palate. However, drawbacks in each of these systems have prevented high-throughput, large-scale studies of palatogenesis in vitro. Here, we report the generation of an immortalized MEPM cell line that maintains the morphology, migration ability, transcript expression and responsiveness to exogenous growth factors of primary MEPM cells, with increased proliferative potential over primary cultures. The immortalization method described in this study will facilitate the generation of palatal mesenchyme cells with an unlimited capacity for expansion from a single genetically-modified mouse embryo and enable mechanistic studies of palatogenesis that have not been possible using primary culture.